PENGARUH LABELISASI SYARIAH DAN BIAYA MU’NAH TERHADAP KEPUTUSAN NASABAH MEMINJAM KREDIT USAHA RAKYAT (KUR) PADA PEGADAIAN SYARIAH CABANG KENDARI - Muhamad Tonasa; Riska Mulya2 (Journal Accounting International Mount Hope, 2025)
The current phenomenon, namely the new product introduced by Pegadaian, namely KUR Syariah, has increased competition between several types of financing in Kendari City. This large amount of financing means there are many options for (customers) of MSME players to choose what they feel will provide the most benefits and convenience. In fact, the large amount of financing available in Kendari City does not have an impact on the number of requests to borrow Sharia KUR funds at the Baruga Unit Sharia Pegadaian and in fact the amount increases every year, starting from its initial introduction in June 2022 until 2024. This means that, even though there is a lot of financing that distributes KUR funds, it is not in line with the theory (hope) that customers will spread out and choose to apply elsewhere, it is the Baruga Sharia Unit Pegadaian that continues to experience an increase in the number of Syariah KUR customers every year. This research aims to determine the influence of sharia labeling and mu'nah fees on customers' decisions to borrow people's business credit at the Kendari Syariah Pegadaian. The data collection technique in this research used questionnaires with a population of 159 active customers. The sampling technique uses random sampling technique with a sample of 40 customers. The method used is quantitative with multiple linear regression analysis. The results of this research show that: 1). Sharia labeling partially has a positive and significant effect on customer decisions, 2). Mu'nah fees partially have a positive and significant influence on customer decisions, 3) Sharia labeling and mu'nah fees simultaneously have a positive and significant influence on customer decisions.